Implementasi Pengujian Theorema Bayes Pada Studi Kasus Pemilihan Smartphone Android - Didik Kurniawan; Feby Eka Febriansyah; Afrizka Amidya (Universitas Lampung, 2018)
Smartphone is internet-enabled mobile that typically provides Personal Digital Assistant (PDA) functionssuch as calendar, to-do books, address books, calculators, and notes. Smartphone has a function thatresembles a computer. In the future, smartphone technology will surpass desktop computer technology,especially in terms of accessing data from internet. With the rapid progress, it prompts android smartphonemanufactures to compete in making products with a variety of types and specifications to provide choicesfor consumers. Theorem Bayes is a method of classifying data, while the basic concept used is a theoremused in statistics to calculate probability. White-box testing is a test case design method that uses the controlstructure of procedural design in obtaining test cases. In conclusion, by using the concept